Leadership challenges in the context of university 4.0. A thematic synthesis literature review - Rocha, Álvaro (2022)
Supported by an environment that is increasingly immersed in digital transformation, universities are facing important organizational changes in both tangible and intangible structures. Digital transformation isn’t all about technology, there is a human side of the story. Leadership is seen as a key issue in any process of change. However, leaders of professional and knowledge-based institutions, like universities, face special demands. The present article aims to synthesize what has been investigated about leadership in the context of University 4.0. A systematic approach was adopted in conducting the literature review. The main body of the article focuses on illustrating five thematic clusters grounded in the literature and identifying co-citation network of each cluster using bibliometrics. Results demonstrate that this is an emerging theme. This paper is the first attempt to systematically review all research that so far has been made available in the broad field of leadership in University 4.0.